An Analytical Study for Assessing Water Productivity in Pre- and Post-Rehabilitation Period of Rural Tank System - B. Anuradha; S. Packialakshmi; Naveen Sanjay; V. Vivekananthan (Advances in Civil Engineering)
Water productivity is the ratio of the amount of water applied to the field in cubic meter and the net return gained in rupees. Increased water productivity leads to an improved occupational value for the farmers. Tank rehabilitation allows for additional water to be added to an irrigation tank, increasing water production. Hence, this study is carried out to assess the net return for a unit of water used in the pre- and post-rehabilitated period of rural tank “Pelasur” in Thiruvannamalai district of Tamil Nadu. The findings reveal that during the post-tank restoration period, a higher percentage of tail reach and marginal farmers benefited. Farmers who irrigate solely with tank water have higher water production since their income per m3 is higher. The significant impact of tank repair was demonstrated using the Statistical Package for Social Science (SPSS-21.0).